Book Reviews (Journal of Finance, 1980)
Abstract Book reviewed in this article: Financial Statement Analysis . By GEORGE FOSTER. Englewood Cliffs Problem and Failed Institutions in the Commerical Banking Industry . By JOSEPH F. SINKEY, JR. The Dow Jones‐Irwin Guide to Modern Portfolio Theory . By ROBERT HAGIN. Forecasting: An Appraisal for Policy‐Makers and Planners . By W. ASCHER. The Basic Theory of Corporate Finance . By KENNETH J. BOUDREAUX AND HUGH W. LONG. Englewood Cliffs The Investment Decisions of Firms . By STEPHEN J. NICKELL. Financing Black Economic Development . By TIMOTHY BATES AND WILLIAM BRADFORD Financial Management: An Introduction . By STEPHEN H. ARCHER, G. MARC CHOATE, AND GEORGE RACETTE.